Filo Arthropoda: abordagem do tema pelos livros didáticos das escolas públicas de Limeira, SP - Xavier, Jessie (Universidade Federal de São Carlos, 2019)
The Phylum Arthropoda constitutes a complex group of invertebrate animals with a wide distribution in environments worldwide, forming the animal kingdom's phylum with the highest number of representatives. In the teaching of Biology, as well as other disciplines, the textbook (TB) remains an important resource for presenting various themes to students, including the "Phylum Arthropoda" of invertebrate beings. Considering the issues surrounding the use of textbooks in the teaching of Science and Biology and the importance of arthropods in various aspects, this study aimed to analyze the treatment of the Phylum Arthropoda in Biology textbooks used by the state public school system in the city of Limeira, SP, and the possible influences of these materials on student learning. For this purpose, ten schools were selected using a sampling method based on regions of the municipality. In total, the educational institutions had six different collections of textbooks in the field, which were analyzed in two ways: first, quantitatively, considering the allocation of pages for the theme, and then qualitatively, through content analysis, following specific criteria. The results suggest some difficulty in generalizing regarding the quality of textbooks, as each criterion of analysis alternated between positive and negative highlights. However, there are reasons to believe that the "Ser Protagonista" and "Biologia Hoje" collections have more positive aspects than other collections, considering the analyzed criteria. On the other hand, the "Biologia - Unidade e Diversidade" collection showed more points to be improved. Studies like this emphasize the importance of a solid initial and continuous training of teachers so that they can have a critical capacity for the selection and use of textbooks in Biology classes, aiming for better results in the teaching and learning process.
Phylum Arthropoda: An analysis of the topic in the textbooks of public schools in Limeira, SP
Keywords: Artrópodes; Livro didático; Ensino de biologia; Análise de conteúdo; Arthropods; Textbook; Teaching Biology; Content analysis; CIENCIAS HUMANAS::EDUCACAO::ENSINO-APRENDIZAGEM::METODOS E TECNICAS DE ENSINO